2012
DOI: 10.1093/treephys/tps092
|View full text |Cite
|
Sign up to set email alerts
|

Norway maple displays greater seasonal growth and phenotypic plasticity to light than native sugar maple

Abstract: Norway maple (Acer platanoides L), which is among the most invasive tree species in forests of eastern North America, is associated with reduced regeneration of the related native species, sugar maple (Acer saccharum Marsh) and other native flora. To identify traits conferring an advantage to Norway maple, we grew both species through an entire growing season under simulated light regimes mimicking a closed forest understorey vs. a canopy disturbance (gap). Dynamic shade-houses providing a succession of high-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 52 publications
4
28
2
Order By: Relevance
“…A pervasive non-native understorey species in the Ohio River Valley, Lonicera maacki , stays green later than any native understorey species (Becker et al 2013). Similarly, the invasive tree Acer platanoides also stays green later than one studied North American congener (Paquette et al 2012). Further, recent work suggests that these non-native species may not play by the same risk–investment rules as native species in the fall.…”
Section: Role Of Climate Change In Phenologically Mediated Invasions:mentioning
confidence: 95%
See 1 more Smart Citation
“…A pervasive non-native understorey species in the Ohio River Valley, Lonicera maacki , stays green later than any native understorey species (Becker et al 2013). Similarly, the invasive tree Acer platanoides also stays green later than one studied North American congener (Paquette et al 2012). Further, recent work suggests that these non-native species may not play by the same risk–investment rules as native species in the fall.…”
Section: Role Of Climate Change In Phenologically Mediated Invasions:mentioning
confidence: 95%
“…Alongside these theoretical developments, a growing body of research focused on plants has found phenological differences, especially in leafing and flowering times, between non-native and native species. Several studies have found that especially early (McEwan et al 2009; Wilsey et al 2011; Throop et al 2012; Wainwright et al 2012) or late (Godoy et al 2009; Fridley 2012; Paquette et al 2012; Pearson et al 2012) phenologies may aid the success of non-native species, while more recent work suggests that non-native species may be the major drivers of longer growing seasons in North America (Wolkovich et al 2013). Here we build on current theoretical perspectives and empirical work to develop predictions of how phenology may enhance plant invasions with climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The plant invasion biology literature has paid considerable attention to one type of variation formulating the phenotypic plasticity hypothesis, which posits that phenotypically plastic species are better able to establish and spread in novel environments (Richards et al 2006;Davidson et al 2011). Several experimental and observational studies have compared native and alien/invasive plants, but their results offer mixed support for this hypothesis, including higher plasticity in invasives, no differences, and even higher plasticity in natives (Funk 2008;Davidson et al 2011;Godoy et al 2011;Palacio-LĂłpez and Gianoli 2011;Paquette et al 2012). On the other hand, the majority of animal studies looking for determinants of alien species' establishment success has focused on the role of abiotic factors and/or mean trait values of the studied species without explicitly accounting for intraspecific trait variation (Duncan et al 2003;Forsyth et al 2004;Hayes and Barry 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic plasticity greatly improves the resistance and the ability to obtain resources of an individual tree seedling (e Silva et al 2012) and also improves the competitive ability in the environment (Paquette et al 2012), thereby laying a solid foundation for the survival and reproduction. Therefore, studying the photosynthetic characteristics of different trees is an effective way to understand the survival mechanisms of adaptation to the light environment (Klein et al 2013, Flexas et al 2014.…”
Section: Introductionmentioning
confidence: 99%